Employee Ownership and Attitudes Toward the Union: An Empirical Study - Long, Richard J. (Relations industrielles / Industrial Relations, 1978)
This article explores the relationship between employee ownership and attitudes toward the union by reporting the results of an empricial study of a unionized Canadian trucking company recently purchased from it s former corporate owner by most of its workers and managers. Results indicated that most workers— both union and non-union— did not believe that unionization was either incompatible with employee ownership or unnecessary.